Insights into agroecological farming practice implementation by conservation-minded farmers in North America - Silva, Erin M.; Wezel, Alexander; Stafford, Caley; Brives, Jeanne; Bosseler, Nathan; Cecchinato, Nicole; Cossement, Camille; Ranaldo, Marzia; Broome, Megan (Frontiers in Sustainable Food Systems, 2023)
Introduction The transformation of our food system towards a more resilient agroecological framework is one of the most pressing needs faced by our global community. Understanding the use of multiple conservation practices is important in the development of research, education, and policy to accelerate their more widespread integration of into farming systems. Methods The aim of this study was to conduct a preliminary investigation of the trends regarding multiple practice adoption of conservation farming practices by conventional and organic farmers engaging with sustainable farming methods. Forty farmers were interviewed regarding their use of conservation practices, as well as their motivations, barriers, and future plans for new implementation and expansion of current practices. Results Farmers spontaneously identified cover crops and vegetation strips as the most frequently used conservation practices; however, upon more specific inquiry, we found that more than 50% of farmers used additional agroecological conservation practices including local crop varieties, intercropping, managed grazing, crop rotations, and no-till, with many farmers using multiple practices. Overall, we found no correlation of organic certification with the number of conservation practices implemented by farmers. The major motivations towards the adoption of practices included improved soil quality and profitability. Main identified barriers included financial means and risk, lack of knowledge, and access to resources. Farmers showed interest in further implementation of additional conservation practices, including expanded use of cover crops, tree plantings, and no-till practices. Discussion Further understanding complementarities, as well as differences in barriers and motivations, can contribute to the design of effective education strategies and financial incentives to promote the simultaneous implementation of agroecological conservation practices.